Modelling financial results based on “green” budgeting principles - Rossano-Rivero, Sue; Oriekhova , Kateryna; Golovko , Olena; Holovko , Violetta (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
Contemporary challenges arising from the global environmental crisis, the transition to a low-carbon economy, economic instability and digital transformation necessitate a rethinking of approaches to financial planning in enterprises.Problem statement. Modelling the financial results of enterprises based on the principles of “green” budgeting makes it possible to combine economic goals with environmental and social objectives. Such an approach meets the requirements of ESG standards and the challenges of European integration processes.Unresolved aspects of the problem. Scholarly research focuses on various directions in the development of budgeting: improving enterprise budgeting systems, applying HR- and gender-oriented approaches, integrating instruments of controlling, strategic management, investment project evaluation, crisis management and ensuring financial security.Purpose of the article is to substantiate and develop a model for forecasting an enterprise’s financial results, integrated with the principles of “green” budgeting, which ensures a balanced combination of financial goals and environmental standards, promotes resource optimisation, and enhances business competitiveness.Presentation of the main material. The object of the study is the system of strategic financial planning of the enterprise, considered from the perspective of integrating environmentally oriented investments, energy efficiency projects, and the implementation of renewable energy sources into financial strategies.Conclusions. The proposed model provides for the allocation of financial resources with consideration for investments in energy-efficient technologies, decarbonisation projects, the implementation of renewable energy sources, and waste management systems. This contributes to reducing operating costs, optimising resource use, and strengthening the enterprise’s environmental reputation. The assessment of financial and economic indicators, taking into account ESG principles, confirmed that “green” budgeting not only improves key financial metrics (profitability, liquidity, asset turnover) but also enhances non-financial indicators related to environmental and social responsibility.The practical value of the work lies in providing recommendations for integrating “green” budgeting into the strategic management system, which can be used by enterprises across various sectors to improve financial stability, environmental performance, and social responsibility.The results obtained can serve as a basis for developing sector-specific methodological guidelines and adapting international ESG standards to the realities of the Ukrainian economy.